Impact of CKD on Female Reproductive Hormones - Mahua Bhaduri; Ippokratis Sarris; Pirro Hysi; Kypros Nicolaides; Freya Baird; Kate Bramham (Kidney International Reports, 2025)
Introduction: Increasing numbers of women with chronic kidney disease (CKD) are using assisted reproductive technology (ART) to conceive, though the mechanisms by which CKD reduces fertility remain unclear. Methods: This study investigated the impact of CKD on female reproductive hormones through an observational cohort study of 100 women with CKD and 57 healthy controls recruited from 4 hospital sites. Clinical data and serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), prolactin, testosterone, estradiol, progesterone, anti-Mullerian hormone (AMH), and β–human chorionic gonadotrophin (β-HCG) were measured during the early menstrual cycle or at convenience for amenorrheic participants. Fertility ultrasounds were also performed, and ethical approval was obtained with participant consent. Results: Compared with healthy controls, patients with CKD had a higher proportion of non-White ethnicity (49.0% vs. 31.8%, P < 0.03), with 22% having undergone renal transplantation. There was no significant difference in age or body mass index (BMI) between the groups. Women with CKD had higher LH levels (5.9 vs. 4.4 IU/l, P < 0.01), which correlated with declining estimated glomerular filtration rate (eGFR) (P < 0.001). AMH levels (13.6 vs. 21.4 pmol/l, P = 0.008) and antral follicle count (AFC) (12.5 vs. 18, P = 0.009) were lower in the CKD group, decreasing with declining eGFR but not after adjusting for age and BMI. Prolactin levels increased with declining eGFR, whereas other hormones showed no significant differences. The AMH-to-AFC ratio did not differ between CKD and controls. Conclusion: This largest prospective study to date on fertility hormonal profiles in CKD underscores the need for longitudinal research to guide informed, timely fertility decisions for women with CKD.